ISLAMIC COUNSELING TECHNIQUES - Rifqi Muhammad (Cross-border, 2019)
This study aims to describe the names, forms and techniques of Islamic counseling from al-Ghazali's perspective. this type of research uses library research on the book of kimiya 'al-sa'adah by Imam al-Ghazali. The results of the study 1) al-Ghazali mentioned the name of the counseling formula with the term kimiya' al-sa'adah/spiritual chemistry; 2) the form of counseling done by al-Ghazali is spiritual counseling; 3) the counseling techniques used are self-knowledge questions; contemplation techniques; mirror technique; imagery technique.